Evaluación en microscopia electrónica de barrido de la dentina superficial, media y profunda después de la aplicación del hipoclorito de sodio con diferentes concentraciones y tiempo - Silva Barrera, Tatiana Elizabeth (2017)
The challenge facing restorative dentistry today is to achieve an intimate bond between restorative materials and dental tissues. At the dentin level this challenge is greater, since the dentin is a fabric that presents a high degree of humidity generating inconveniences in the adhesion, in addition, acid etching that not only eliminates the layer of dentin barrel, but also, totally demineralizes some Micrometers of the dentinal tubules and in many cases adhesive systems fail to fully enter. Deproteinization with the use of sodium hypochlorite eliminates the organic part of the dentin, helping to optimize the quality of the hybrid layer and improving the marginal sealing. Objective: To evaluate the scanning electron microscopy of the superficial, medium and deep dentin after application of sodium hypochlorite in different concentrations and time. Method: We selected 45 moral third parties, which were maintained in physiological serum. They were randomly selected for preparation in both superficial, medium and deep dentin. Dental pieces were measured according to the different depths of dentin and periapical radiographs were taken. The dental pieces were trimmed, radiographs were taken and the dentin surfaces were polished and then placed in the ultrasound for 10 min at 50w. Sodium hypochlorite was applied at 5.25 percent and 1percent at the respective dentinal surfaces for 30 and 60s. In a container with silica gel the dental pieces were placed for 48 hours.